Political thought in Modern India/ edited by Thomas Pantham and Kenneth L. Deutsch - "Pantham, Thomas (ed.);Deutsch, Kenneth L. (ed.)" (New Delhi, 2013)
The twenty stimulating and original essays in this volume provide a comprehensive analysis of the main strands of modern Indian political thought.The thinkers dicussed are Rammohun Roy, Dayananda Saraswati, Bankimchandra Chattopadhyay, Ranade, Phule, Tilak, B R Ambedkar, Tagore, Sri Aurobindo, M N Roy, Jawaharlal Nehru and Gandhi. Separate essays are devoted to the Hindu and Muslim traditions in Indian political thought, Hindu nationalism, and the ideologies of the Communist and Sarvodaya movements. A significant feature of these essays is that they study each thinker or movement in the relevant socio-historical context as also examine the consequences and impact of modern Indian political theories, These are analysed from a world-hostorical and, to some extent, a political economy perspective.The essays in this collection highlight two major streams in modern Indian political thoughtone which favoured the adoption or adaptation of western political traditions and the other which sought to evolve indigenous or alternative formulations. The overall conclusion that emerges from this volume is that in order to formulate an adequate political philosophy for the modern age, both the western and Indian traditions have to be taken into account. In this context, some of the essays highlight the contemporary global relevance of Gandhis socio-political ideas.This book is a major contribution to modern political philosophy. It will be of great value to students and teacher of political science.
Keywords: "Political thought, India"